Role of transporters in regulating mammalian intracellular inorganic phosphate - Jennings, Michael L. (Frontiers in Pharmacology, 2023)
This review summarizes current understanding of the role of plasma membrane transporters in regulating intracellular inorganic phosphate ([Pi]In) in mammals. Pi influx is mediated by SLC34 and SLC20 Na+-Pi cotransporters. In non-epithelial cells other than erythrocytes, Pi influx via SLC20 transporters PiT1 and/or PiT2 is balanced by efflux through XPR1 (xenotropic and polytropic retrovirus receptor). Two new pathways for mammalian Pi transport regulation have been described recently. 1) In the presence of adequate Pi, cells continuously internalize and degrade PiT1. Pi starvation causes recycling of PiT1 from early endosomes to the plasma membrane and thereby increases the capacity for Pi influx. 2) Binding of inositol pyrophosphate InsP8 to the SPX domain of XPR1 increases Pi efflux. InsP8 is degraded by a phosphatase that is strongly inhibited by Pi. Therefore, an increase in [Pi]In decreases InsP8 degradation, increases InsP8 binding to SPX, and increases Pi efflux, completing a feedback loop for [Pi]In homeostasis. Published data on [Pi]In from magnetic resonance spectroscopy indicate that the steady state [Pi]In of skeletal muscle, heart, and brain is normally in the range of 1-5 mM, but it is not yet known whether PiT1 recycling or XPR1 activation by InsP8 contribute to Pi homeostasis in these organs. Data on [Pi]In in cultured cells are variable and suggest that some cells can regulate [Pi] better than others following a change in [Pi]Ex. More measurements of [Pi]In, influx, and efflux are needed to determine how closely, and how rapidly, mammalian [Pi]In is regulated during either hyper- or hypophosphatemia.